SISTEM INFORMASI PENERIMAAN MURID BARU (SPMB) BERBASIS WEBSITE PADA SMP NEGERI 1 TANJUNG AGUNG - Sihombing, Grace Christine; Yulianingsih, Evi (Rang Teknik Journal, 2026)
Abstract : SMP Negeri 1 Tanjung Agung is one of the public junior high schools in Muara Enim Regency that experiences an increase in the number of new student registrants every year. Based on school administrative data, the number of prospective students in the 2024 school year was recorded at 466 students and increased to 687 students in the 2025 school year. However, the New Student Admission System (SPMB) process is still carried out manually using registration forms that must be obtained and filled out directly at the school. This situation causes various problems, such as limited service time, backlogs of applicants, the risk of data loss or damage, and inefficient data management and storage processes. This study aims to develop a website-based New Student Admission Information System (SPMB) at SMP Negeri 1 Tanjung Agung that can manage the registration process in an integrated manner, starting from online registration, filling in prospective student data, uploading required files, administrative selection, to the announcement of admission results. The system development method used is the waterfall method, which includes the stages of requirements analysis, design, implementation, testing, and maintenance. The results of this study are expected to improve the effectiveness and efficiency of the SPMB committee, facilitate parents or guardians of prospective students in registering, and improve the quality of data management and information services at SMP Negeri 1 Tanjung Agung in a transparent and structured manner. Keywords: Information System, New Student Admission, Website, Waterfall